PERAN GANDA PEREMPUAN DALAM KEHARMONISAN RUMAH TANGGA: Studi Kasus di Desa Ngabar Kecamatan Siman Kabupaten Ponorogo - Alfiati, Lilik; Mahmudah, Ummi (Ngabari: Jurnal Studi Islam dan Sosial, 2020)
This study aims to determine the effect of womens dual roles on family harmony. A qualitative descriptive approach was used in this study. The results show the factors that cause women to play a dual role, namely: the economic needs of her family are increasing, she wants to use the knowledge she has, she wants to help her husband meet family needs, she works to fill spare time, her husband dies, her husband an unemployed person. It is not true that the opinion that says that if women work outside the home, the result is that the family situation is not harmonious, because from this research it is proven that the informants families remain harmonious even though they are women who play a dual role. But there are impacts, namely: the closeness to family members, especially with children is reduced, the division of labor at home is reduced, and interaction with the community is also reduced.